The Fatty Acid Profile in Patients with Newly Diagnosed Diabetes: Why It Could Be Unsuspected. (11th September 2017) - Castro-Correia, C.; Sousa, S.; Norberto, S.; Matos, C.; Domingues, V. F.; Fontoura, M.; Calhau, C.
Abstract : Context . Several studies have shown a link between proinflammatory activity and the presence or deficit of some fatty acids. Inflammation is associated with several diseases including diabetes. Objective . To characterize and compare the fatty acids profiles in children with inaugural type 1 diabetes, diabetic children (at least 1 year after diagnosis), and healthy children. Design . Plasma fatty acids profiles in children with inaugural diabetes, children with noninaugural diabetes, and controls, all of whom were prepubescent with a BMI < 85th percentile, were evaluated. Results . Omega-3 fatty acid levels were higher in recently diagnosed subjects with diabetes than in controls. The ratio of omega-6/omega-3 fatty acids was higher in the control population. Omega-6 fatty acid levels were higher in the nonrecent diabetic subjects than in the children with recently diagnosed diabetes, and the levels were higher in the nonrecent diabetes group compared to the control group. Conclusion . Our findings showed higher levels of alpha-linolenic acid, EPA, and DHA, as well as mono- and polyunsaturated fatty acids, in diabetic children. These findings reinforce the importance of precocious nutritional attention and intervention in the treatment of diabetic children.